Oxidative stress biomarkers after a single maximal test in blind and non-blind soccer players - Viana Gomes, D.; Santos Vigário, P.; Lima Piazera, B. K.; Pereira Costa, F.; Vaisman, M.; Salerno Pinto, V. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The aim of this study was to compare oxidative stress biomarkers, antioxidant capacity, muscle damage and hormone response between vision impaired and non-vision impaired athletes after a single maximal exercise test. METHODS: Eight vision impaired and fifteen non-vision impaired athletes performed a maximal aerobic test with blood collected before and after. RESULTS: Non-vision impaired athletes displayed greater aerobic capacity than blind individuals (P<0.05). Lactate increased by four-fold, while creatine kinase and gamma-glutamyltransferase as well as the oxidative stress biomarkers and antioxidants were unchanged. Cortisol increased, but testosterone and their ratio were not altered. Differences were observed for alanine transaminase and aspartate transaminase, which were increased only in non-blind athletes. CONCLUSIONS: Our data suggest that blind soccer players, in comparison to those with vision, experienced less cellular damage.